Exosomes from cisplatin-induced dormant cancer cells facilitate the formation of premetastatic niche in bone marrow through activating glycolysis of BMSCs - Xu, Jiaqi; Feng, Xiang; Yin, Na; Wang, Lujuan; Xie, Yaohuan; Gao, Yawen; Xiang, Juanjuan (Frontiers in Oncology, 2022)
Lung cancer is the leading cause of cancer-related deaths worldwide. Chemotherapy kills most cancer cells; however, the residual cells enter into dormant state. The dormant cancer cells can be reactivated under specific circumstances. The "premetastatic niche" that is suitable for colonization of cancer cells is formed before the arrival of cancer cells. Tumor-derived exosomes are the main mediators of tumorigenesis. We are aiming to elucidate the roles of exosomes from cisplatin-induced dormant lung cancer cells in the formation of pre-metastatic niches in bone marrows. We performed differential proteome in dormant A549 cell- and A549 cell-derived exosomes. Non-targeted metabolomics and RNA sequencing were performed to explore the molecular and metabolic reprogramming of BMSCs. The growth and metastasis of A549 cells in vivo were monitored by bioluminescence imaging. We found that IGF2 and IGFBP2 were up-regulated in dormant A549 cell-derived exosomes. BMSCs that uptook exosomes from dormant A549 cells showed enhanced glycolysis and promoted the growth and metastasis of A549 cells through IGF-1R induced metabolic reprogramming. Inhibition of production of lactate and IGF-1R signaling can suppress the growth and metastasis of A549 cells from bone marrow. Overall, we demonstrated that BMSCs formed premetastatic niche upon uptaking exosomes from cisplatin-induced dormant lung cancer cells. BMSCs promoted lung cancer cell growth and metastasis through reverse Warburg effect.